Nuclear - Hawkes, Nigel (London ; New York : F. Watts, 1981)
Discusses the scientific and technological background and the advantages and disadvantages of the powerful and controversial form of energy released through the splitting of the atom.
Includes index.
Title on spine: Nuclear energy.
Keywords: Nuclear energy -- Juvenile literature; Nuclear energy